Determinants of Tax Evasion in Ghana: 1970-2010 - Betty Annan; William Bekoe; Edward Nketiah-Amponsah (International Journal of Economic Sciences and Applied Research, 2013)
This paper investigates the factors that determine tax evasion in Ghana using time series data covering the period 1970-2010. Employing the currency demand approach, we obtained the estimates of the shadow economy and the level of tax evasion for the entire period. Using the bounds test technique of cointegration we found that the variables included in our ARDL model are bounded together. The short-run model indicates that per capita income, the average tax rate, age and inflation were positively and significantly associated with tax evasion while gender showed an inverse and significant relationship with tax evasion. The error correction term was negative, statistically significant and suggests that 45 per cent of the deviation from equilibrium tax evasion is corrected each year. In addition, the Granger causality test indicates that tax and inflation rates aid in predicting future levels of tax evasion in Ghana. The paper further discusses the policy implications of the findings.
Keywords: H26; H41; O23; 330; tax evasion; bounds testing; error correction; granger causality; Ghana